Quality Management of Private Vocational High Schools in Tarakan City Yogyakarta: Faculty of Education and Psychology, Yogyakarta State University, 2024 - Syahrani Syahrani; Setya Raharja (Green Publisher Indonesia, 2025)
This research aims to describe: (1) The quality of Private Vocational High School (SMK) in Tarakan City, and (2) implementation of quality management in Private Vocational High School (SMK) in Tarakan City. The research uses a qualitative approach with a phenomenological type. This research was carried out at three private vocational school, namely North Kalimantan Health Vocational School, Indonesian Maritime Vocational School and Paguntaka Vocational School. The research subjects were school principals, teachers and administrative staff of private vocational school in Tarakan City by conducting in depth interview, partisipatory observation and document study. Triangulation of sources and methods is used to ensure the validity of the data. The data analysis technique follows the interaction model from Miles and Hubbermanwhich includes: reduction, presentation and drawing conclusions. The results of this research show the following (1) quality policy is implemented through the socialization of vision and mission, learning supervision, internship program and continous evaluation with the main focus of the policy being to increase student competency and suitability of education to the needs of the world of work, although constrained by limited funds and human resources which are overcome by internal training and industrial cooperation. (2) The implementation of quality management follow the principal of Total Quality Management (TQM) by involving all school element and external stakeholderssuch as industry and parents, with evaluation based on graduation data and job absorption, while budget and facility limitations are overcome through stakeholder collaboration.